The Effect of Combination Of Progressive Muscle Relaxation And Nature Sound Music Therapy On Sleep Quality Of Menopaused Women - Alvina Cornelia Sugijantoro; Rahayu Anggraini; R. Khairiyatul Afiyah (Journal of Applied Nursing and Health, 2022)
Background: Introduction. Menopause is a critical process that every woman will experience. Decreased function of female organs occurs because they cannot produce the hormones esterogen and progesterone, causing psychological and physiological symptoms. One of the physiological symptoms is sleep quality disorders, which if not handled properly will cause decreased concentratio, anxiety and stress. Pharmacological and non pharmacological theraphy to help postmenopausal women reduce their sleep disorders. The study aimed to determine the effect of combination therapy of progressive muscle relaxation and nature sound music therapy on sleep quality in postmenopause Methods: Quasy-Experiment research design. Population is menopause with a total of 220 people. The sample size is 102 respondents, the sampling is simple random sampling. The treatment group in combination therapy of progressive musc;e relaxation and nature sound music therapy 15-20 minutes; the control group was not given any intervention. The wariavle studied was the value of sleep quality obtained from the results of the questionaire(Pittsburgh Sleep Quality Index). The analysis used the Wilcoxon Signed Test for pre and post treatment and the Mann-Whitney test to determine the difference between the experimental group and the control group with a significant α <0,05. Results: The results of the sleep quality analysis using the Wilcoxon Signed Rank Test, p value 0,000 in the treatment group and p value 0,215 in the control group. The results of the analysis using the Mann-Whitney test obtained a p value  of 0,000 on the value of sleep quality between the treatment group and the control group Conclusion: Combination therapy of progressive muscle relaxation and nature sound music therapy is effective for reducing the value of sleep quality disorders in menopausa women, ang this technique is easy to do, so it Can be applied as a nursing intervention at the puskesmas for the development of nursing knowledge in services